Composition of Fishing Gear Pengerih at Day and Night in Meskom Village, Bengkalis District - Dian Agustin; Bustari Bustari; Alit Hindri Yani (Tropical Marine Enviromental Sciences, 2023)
Pengerih is one of the trapping gears used by fishermen in Meskom Village. The purpose of this study was to determine the composition of the catch of Pengerih including the type and weight of fish caught during the day and night. This research was conducted in September 2022 in Meskom Village, Bengkalis Regency. The method used in this research is the survey method. The analysis used is by calculating the level of main catch and bycatch using the formulation of Akiyama. Based on the results of the study, it was found that the catch of curler gear was 9 types with a total catch of 5.030 fish with a total weight of 51,08 kg. The dominant types of catch during the study were red shrimp (Parapenaeus longirostris) 1.272 fish weighing 10,64 kg, striped shrimp (Parapenaeopsis sculptilis) 1,158 fish weighing 9,71 kg, white shrimp (Panaeus merguiensis) 1,115 fish weighing 9,34 kg, thorn shrimp (Panulirus sp) 883 fish weighing 7,34 kg, Moustached thryssa (Engraulis mystax) 302 fish 3,84 kg. While the bycatch consisted of print shrimp (Harpiosquilla raphidea) 39 fish weighing 1,46 kg, Bombay duck (Harpodon nehereus) 75 fish weighing 5,42 kg, Panna croaker (Otolithoides microdon) 93 fish weighing 1,46 kg, Shorthead hairfin anchovy  (Setipinna breviceps) 93 fish and weighing 1.87 kg. If you look at the results of the catch more tend to be a lot of catches at night 2.813 fish weigh 28.84 while during the day 2.217 fish weigh 22.24 kg